Role of Maritime Public Policy on The Economic Development of Coastal Communities in Tanjungpinang City Area - Tessa Citrani; Muhammad Tri Syaputra (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2024)
Public policy plays a significant role in the development of coastal communities, particularly in areas heavily reliant on maritime resources. This research examines the role of maritime public policy in improving the economic welfare of coastal communities in Tanjungpinang City, located in the Riau Islands, Indonesia. With a population of over 230,000, Tanjungpinang is an archipelago whose residents are largely dependent on fisheries, marine tourism, and trade. The study highlights the importance of Law No. 32 of 2014 on Maritime Affairs and how policies derived from it aim to harness the potential of marine resources to benefit local economies through the blue economy principles. However, despite the clear goals of these policies, challenges in implementation persist. This study utilizes a qualitative approach, combining document analysis, interviews with local stakeholders, and surveys from coastal communities. The research finds that while maritime policies have facilitated several empowerment programs, such as the distribution of fish seeds and awareness campaigns, there are gaps in the infrastructure and workforce development needed to sustain these initiatives. Additionally, local communities show varying levels of engagement with the policies, which affects the overall impact on economic development. The study concludes that while maritime public policies have a positive influence on the economic development of coastal communities in Tanjungpinang City, their full potential can only be realized through continued investments in infrastructure, human resources, and better alignment with the local culture. Effective implementation requires ongoing supervision and adaptation to ensure sustainable growth in the region's maritime sectors.